Destination Quality and Tourist Loyalty: The Role of Destination Value as Mediating Variable - Suprina, Rina; Dhana, Irgi Resa Widia; Gaffar, Vanessa; Disman, Disman; Kusumah, AHG (Institut Pariwisata Trisakti, 2024)
This research analyzes the influence of destination quality and destination value on tourist loyalty in the city of Bandung, Indonesia, and tests whether destination value mediates the relationship between destination quality and tourist loyalty. The type of research chosen is quantitative with a descriptive verification approach using SEM PLS. The population for this research is domestic tourists in the city of Bandung. From the analysis of 196 respondents, the majority were women, aged 18-25 years, and had a high school education. The results show a high assessment of the quality of eating places and the level of tourist loyalty. Public transportation accessibility received a low rating, and the lowest average score on the Time Value Variable. Hypothesis analysis shows a positive and significant influence between destination quality and tourist loyalty. Apart from that, there is a positive and significant influence between destination quality and destination value, and between destination value and tourist loyalty. The findings show that destination value mediates the relationship between destination quality and tourist loyalty, emphasizing the importance of strengthening destination value elements to increase tourist loyalty in Bandung City. Keywords: destination quality, destination value, tourist loyalty, urban tourism, city branding